Brain temperature and exercise performance - Nybo, L. (Experimental Physiology, 2012)
Events arising within the central nervous system seem to be a major factor in the aetiology of hyperthermia-induced fatigue. Thus, various studies with superimposed electrical nerve stimulation or transcranial magnetic stimulation have shown that both passive and exercise-induced hyperthermia will impair voluntary motor activation during sustained maximal contractions. In humans, the brain temperature increases in parallel with that of the body core, making it very difficult to evaluate the independent effect of the cerebral temperature. Experiments with separate manipulation of the brain temperature in exercising goats indicate that excessive brain hyperthermia will directly affect motor performance. However, several homeostatic changes arise in parallel with hyperthermia, including factors that may influence both peripheral and central fatigue, and it is likely that these changes interact with the inhibitory effect of an elevated brain temperature.